The First Sale Doctrine and Public Library Provision of Print and Electronic Books - Reimers, Imke; Waldfogel, Joel (The Review of Economics and Statistics, 2024)
Abstract Libraries deliver the majority of US book consumption, and library costs are kept low by the first sale doctrine's guarantee that libraries can lend print books without additional compensation to publishers. However, publishers' decisions to restrict ebook access may threaten libraries. We measure impacts of holdings on circulation; and library holdings choices suggest that library managers value instances of ebook circulation more than print. We use a structural model of patron demand and library holdings to show that more restrictive print book terms would have ten times the negative patron welfare impact of an equivalent restriction on ebooks.